Music, Mind, and Embodiment 11th International Symposium, CMMR 2015, Plymouth, UK, June 16-19, 2015, Revised Selected Papers - Kronland-Martinet, Richard; Aramaki, Mitsuko; Ystad, Sølvi (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the thoroughly refereed post-conference of the 11th International Symposium on Computer Music Modeling and Retrieval, CMMR 2015, held in Plymouth, UK, in June 2015. The 30 full papers presented were carefully reviewed and selected from 126 submissions. This year's post symposium edition contains peer-reviewed and revised articles centered around the conference theme "Music, Mind, and Embodiment". It is divided into 6 sections devoted to various sound and technology issues with a particular emphasis on performance, music generation, composition, analysis and information retrieval, as well as relations between sound, motion and gestures and human perception and culture.